MANEJO DE LA INFECCIÓN DEL TRACTO URINARIO EN NIÑOS - Rojas Pérez, Lino Arturo (2023)
Introduction. Urinary tract infection is a frequent and significant clinical problem in the pediatric population. They are classified into acute pyelonephritis, cystitis, and asymptomatic bacteriuria. Objective. To identify the most appropriate treatment for pediatric urinary tract infections, in accordance with the most recent and solid scientific evidence. Methods. In the development of this non-systematic review article, the databases PubMed, Scopus, DynaMed, and UpToDate were used. As for the inclusion criteria, articles written in the last five years, both in English and Spanish language, were considered as long as the full text was accessible. This selection included clinical studies, randomized clinical trials, systematic reviews and meta-analyses. Results. In total, 2236 articles were found during the entire information search process. Of these 2236, 2201 articles that did not meet the inclusion criteria were discarded, and 35 articles were used for this research on the management of urinary tract infection in children. Discussion. Urinary tract infection is a common problem in childhood. The clinical symptoms can be unspecific in babies and small children; however, in older children, the symptoms are clearer and include fever, lower back pain, suprapubic pain, dysuria, polyuria, among others. The confirmatory diagnosis is made through urine culture. Timely treatment reduces the risk of subsequent complications. Conclusions. This review provides a comprehensive guide for the effective management of urinary tract infections in children, considering both accurate diagnosis and appropriate treatment.